'The development of Irish identity: political aspiration and literary conceptions, 600-919 - MEIGHAN, BRENDAN JAMES (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2020)
This thesis examines the development of an Irish identity in the early medieval period. It covers roughly three centuries, from 600 to 919, and it focuses for the most part on the formation of an Irish political identity, as expressed most clearly in the idea of a kingship of all-Ireland. It also explores more general questions of identity in Ireland at this time, with specific reference to the complex relationship between Irishness and Gaelicness.
APPROVED
Keywords: Ireland; Identity; Early Medieval